Cooperation behaviour and innovation performance in the Nigerian manufacturing industry - Abiodun A. Egbetokun (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Analysing the relationship between firms' openness to external knowledge and their innovation performance is nothing new. What is new is studying how this relationship fares in latecomer economic contexts such as Nigeria, and that is the focus of this paper. Using unique micro-level innovation data, it is shown, as the existing literature suggests, that firms are more likely to innovate when they access external knowledge either through formal or through informal interactions. However, innovative firms that exploit external knowledge do not necessarily enjoy greater innovation benefits than those that do not. Thus, while openness to external knowledge might help firms to become better at innovating, it does not assist them in reaping the benefits derivable from their innovation efforts. Moreover, different innovation types are essentially the same with respect to the effect that network resources have on them. Thus, it makes little sense to engage network partners selectively for certain innovation types at the expense of others.
Keywords: O31; L14; L60; 330; innovation; networking; openness; collaboration; external knowledge; Nigeria; manufacturing industry; Innovation; Wissenstransfer; Soziales Netzwerk; Verarbeitendes Gewerbe; Nigeria